Morphological and Physiological Responses of Clinacanthus Nutans Under Different Light Conditions - Hanafi, Hasya Diyanah; Pa'ee, Furzani (Journal of Sustainable Natural Resources, 2022)
Difference of light conditions resulted in different morphological and physiological responses of plants. This study is proposed to determine the response of Clinacanthus nutans under different light condition as the results of plant defense mechanism. Observation done morphologically shows that samples under condition A appear bigger, longer, higher and pale in colour. Meanwhile, for physiological analysis, shows that there is difference in chlorophyll content based on different condition (0.83 ± 0.463 Ca, 1.46 ± 0.740 Cb and 0.03 ± 0.015 carotenoids for condition A, and 0.50 ± 0.321 Ca, 1.47 ± 0.539 Cb and 0.03 ± 0.105 carotenoids for condition B) and samples under condition A contain higher photosynthetic rate as a result of higher dry matter content (0.27 ± 0.017) in plants.